First report on tick-borne pathogens detected in ticks infesting stray dogs near butcher shops - Ali, Abid; Ullah, Shafi; Numan, Muhammad; Almutairi, Mashal M.; Alouffi, Abdulaziz; Tanaka, Tetsuya (Frontiers in Veterinary Science, 2023)
Public health is a major concern for several developing countries due to infectious agents transmitted by hematophagous arthropods such as ticks. Health risks due to infectious agents transmitted by ticks infesting butcher-associated stray dogs (BASDs) in urban and peri-urban regions have been neglected in several developing countries. This study for the first time adopted to assess public health risks due to ticks infesting BASDs in Pakistan's urban and peri-urban areas. Altogether, 575 ticks (390 from symptomatic and 183 from asymptomatic BASDs) collected from 117 BASDs (63 symptomatic and 54 asymptomatic) were comprised of four hard tick species. A subset of each tick species extracted DNA was subjected to PCR to amplify the 16S rDNA and cox1 sequences of the reported tick species, as well as bacterial and protozoal agents. Tick’s 16S rDNA and cox1 sequences showed 99-100% identities and clustered with the sequence of corresponding species from Pakistan and other countries in phylogenetic trees. Among the screened 271 tick’s DNA samples, Anaplasma spp. were detected in 54/271 (19.92%) samples, followed by Ehrlichia spp. (n = 40/271, 14.76%), Rickettsia spp. (n = 33/271, 12.17%), Coxiella spp. (n = 23/271, 4.48%), and Hepatozoon canis (n = 9/271, 3.32%). Obtained sequences and phylogenetic analyses revealed that the detected pathogens in ticks were Ehrlichia minasensis, Ehrlichia sp., Hepatozoon canis, Coxiella burnetii, Coxiella sp., Anaplasma capra, Anaplasma platys, Anaplasma sp., Rickettsia massiliae, ‘Candidatus Rickettsia shennongii’, and Rickettsia aeschlimannii. Tick-borne pathogens such as E. minasensis, H. canis, A. capra, A. platys, and R. aeschlimannii were DNA based detected for the first time in Pakistan. This is the first report on public health risks due to ticks infesting BASDs. These results not only apprised regarding the occurrence of novel tick-borne pathogens in the region but also unveiled initial evidences regarding zoonotic threats to public health as well as domestic life.